Perlindungan Hukum dan Psikologi Terhadap Anak Jalanan Dalam Perspektif HAM - Eva Dwi Yuliani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The problem of street children is not only the government's responsibility but also the responsibility of all of us as a society. The importance of maintaining the mental and psychological aspects of street children is very necessary so that they can continue living as children with a healthy mentality like children in general. Good mental health in street children will help their social and economic participation. This research uses a normative juridical method, which means an approach carried out by reviewing and studying statutory regulations, especially laws related to child protection. Factors causing the existence of street children are poverty factors, family factors, and environmental factors. Street children often experience complex mental stress, mental pressure or trauma. Difficult real life results in multiple traumas, exile, difficult living conditions, torture, oppression, psychological, physical violence, sexual violence are the traumas felt by street children. Seeing the many problems that arise in the lives of street children, it seems necessary to take follow-up action to deal with the psychological problems of street children, which can be done by organizing child empowerment which can be done through activities held by children's shelters. The purpose of establishing a children's empowerment house is to provide assistance to street children in dealing with their life problems and find solutions to fulfill the life needs of street children. Empowerment can protect the psychology of street children, where coaching street children is expected to change the negative thinking patterns of street children into positive ones.